ANALISIS DAYA SAING JERUK SIAM DALAM MENDUKUNG PENGEMBANGAN KOMODITAS BUAH UNGGULAN DI BANYUWANGI - Azizah, Laily Nur; Soetriono, Soetriono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
Siamese oranges are a fruit commodity that is quite popular with a consumption growth rate of 2.5%  from 2018 to 2022. This condition must be balanced with the availability of local oranges in Indonesia, without increasing orange imports. Orange production in Banyuwangi is quite high in Tegaldlimo District, reaching 201,821.5 tons in 2018, eventhough in 2019 it decreased to 91,991.9 tons. The objectives of this research are to determine the competitiveness of Siamese oranges in Banyuwangi, to determine the sensitivity of the competitiveness of Siamese oranges in Banyuwangi, and to formulate a commodity development model for Siamese oranges in Banyuwangi. The methods used in this research were analysis of private benefits (PP), private cost ratio (PCR), social benefits (SP), and domestic resource ratio (DRCR). Based on the results of the analysis, it is known that the private profit obtained is IDR111,183,814 while the social benefits obtained is  IDR362,759,134. The PCR value is 0.67 and the DRCR value is 0.37. It is also noticed that A 25% and 50%  reduction in the price of Siamese oranges from the normal price has caused a loss in private profits and caused a PCR value more than 1, whereas in the scenario of a 30% increase in the price of inorganic fertilizer, it has caused a negative value in private profits and a PCR value more than 1. Development of Siamese orange farming in the Regency Banyuwangi is encouraging with combination of strategy intensive agricultural extension and increase production output in terms of quantity, quality and continuity of production. Keywords:  competitiveness, siamese oranges, superior commodities